Oral microbiota and oral squamous cell carcinoma: a review of their relation and carcinogenic mechanisms - Sukmana, Bayu Indra; Saleh, Raed Obaid; Najim, Maryam Abdulrahman; AL-Ghamdi, Hasan S.; Achmad, Harun; Al-Hamdani, Mais Mazin; Taher, Abbas AY.; Alsalamy, Ali; Khaledi, Mansoor; Javadi, Kasra (Frontiers in Oncology, 2024)
Oral Squamous Cell Carcinoma (OSCC) is the most common type of head and neck cancer worldwide. Emerging research suggests a strong association between OSCC and the oral microbiota, a diverse community of bacteria, fungi, viruses, and archaea. Pathogenic bacteria, in particular Porphyromonas gingivalis and Fusobacterium nucleatum, have been closely linked to OSCC. Moreover, certain oral fungi, such as Candida albicans, and viruses, like the human papillomavirus, have also been implicated in OSCC. Despite these findings, the precise mechanisms through which the oral microbiota influences OSCC development remain unclear and necessitate further research. This paper provides a comprehensive overview of the oral microbiota and its relationship with OSCC and discusses potential carcinogenic pathways that the oral microbiota may activate or modulate are also discussed.